Food usurpation by waterfowl and waders - Amat, Juan A (Wildfowl, 1990)
Both waterfowl and waders typically aggregate in mixed-species foraging flocks. When foraging, individuals in groups can use the information provided by other individuals, so that they can copy the foraging modes and/or locations or even steal the food previously procured by the other individuals. The prevalence of feeding by scrounging by waterfowl and waders varies in association with some factors which make more or less likely the occurrence of scroungers when individuals of these groups forage in flocks. When food requires short handling times and is clumped in patches, there is the possibility of the development of imitative (copying) foraging tactics; when food requires longer handling times, there is possibility for a more exploitative foraging tactic (kleptoparasitism). In between these two situations other cases may occur, such as supplanting from feeding sites. The usurpation of food, either directly (kleptoparasitism) or indirectly (copying, supplanting), may have some impact on the rates of food intake of usurped individuals. To reduce such impact, usurped individuals may adopt behavioural strategies. As these strategies might be costly, there would be some tradeoff between their adoption and feeding efficiency.